Isolation and molecular identification of biosurfactant producing soil bacteria / Nur Amalina Niza Zamani - Zamani, Nur Amalina Niza (2019)
Biosurfactants are amphiphilic compound, having hydrophilic and hydrophobic moieties enabling them to reduce surface and interfacial tension at the surface. Their unique properties are applied in various industries such as foaming and wetting agents, emulsifiers, detergents and bioremediation. A total of 98 isolates showed biosurfactant activity using hemolytic assay but only 45 isolates demonstrated surfactant activity in drop collapse test and oil spreading assay.